2017
DOI: 10.1016/j.molmet.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL8 promotes the ability of ANGPTL3 to bind and inhibit lipoprotein lipase

Abstract: ObjectiveSeveral members of the angiopoietin-like (ANGPTL) family of proteins, including ANGPTL3 and ANGPTL8, regulate lipoprotein lipase (LPL) activity. Deficiency in either ANGPTL3 or ANGPTL8 reduces plasma triglyceride levels and increases LPL activity, whereas overexpression of either protein does the opposite. Recent studies suggest that ANGPTL8 may functionally interact with ANGPTL3 to alter clearance of plasma triglycerides; however, the nature of this interaction has remained elusive. We tested the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
176
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(188 citation statements)
references
References 47 publications
(112 reference statements)
10
176
1
1
Order By: Relevance
“…Moreover, VAT accumulation and a higher VAT/ SAT ratio may also be associated with increased chronic low-grade systemic inflammation, which could further increase betatrophin synthesis [25,26,31]. Correspondingly, elevated betatrophin levels may contribute toward the pathogenesis of dyslipidemia, which is one of the most important risk factors for CAD, while in vitro and in vivo studies have suggested that betatrophin could aggravate hypertriglyceridemia by promoting the ability of ANGPTL3 to bind and inhibit LPL [5,6,35]. Clinical studies have also confirmed that betatrophin levels are significantly and positively related to TG and LDL-C levels and inversely related to HDL-C levels in children and patients with diabetes [1,7,36,37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VAT accumulation and a higher VAT/ SAT ratio may also be associated with increased chronic low-grade systemic inflammation, which could further increase betatrophin synthesis [25,26,31]. Correspondingly, elevated betatrophin levels may contribute toward the pathogenesis of dyslipidemia, which is one of the most important risk factors for CAD, while in vitro and in vivo studies have suggested that betatrophin could aggravate hypertriglyceridemia by promoting the ability of ANGPTL3 to bind and inhibit LPL [5,6,35]. Clinical studies have also confirmed that betatrophin levels are significantly and positively related to TG and LDL-C levels and inversely related to HDL-C levels in children and patients with diabetes [1,7,36,37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, at the liver increased ANGPTL8 forms complexes with ANGPTL3 to inactivate LPL at the site of oxidative tissues (i.e. skeletal muscle) to promote lipid oxidation (23).…”
Section: Discussionmentioning
confidence: 99%
“…These triglycerides are digested by lipoprotein lipase [15][16][17][18][19]. Chi et al used NanoBiT to demonstrate the association between lipoprotein lipase and angiopoietin-like 3 (ANGPTL3) induced by ANGPTL8 [20]. They further described that the association inhibits the digestion activity of lipoprotein lipase.…”
Section: Application Of Nanobit For Analysis Of Protein-protein Intermentioning
confidence: 99%